The imperial presidency$1 (Bs enablers: Why executive power grows unchecked s - Vladeck, Stephen I. (Foreign Affairs)
In 1866, the U.S. Supreme Court handed down its landmark decision in Ex parte Milligan, which barred the federal government from trying civilians in ad hoc military tribunals when civilian courts were available. Writing for the majority, Justice David Davis spent several pages explaining the dangers of an unchecked executive. The United States, he said, (3z(Bhas no right to expect that it will always have wise and humane rulers, sincerely attached to the principles of the Constitution.(3y (BInstead, (3z(Bwicked men, ambitious of power, with hatred of liberty and contempt of law, may fill the place once occupied by Washington and. Reproduced s